Ensemble Algorithm for Parametrized Flow Problems with Energy Stable Open Boundary Conditions - Takhirov, Aziz; Waters, Jiajia (Journal of computational methods in applied mathematics, 2020)
We propose novel ensemble calculation methods for Navier–Stokes equations subject to various initial conditions, forcing terms and viscosity coefficients. We establish the stability of the schemes under a CFL condition involving velocity fluctuations. Similar to related works, the schemes require solution of a single system with multiple right-hand sides. Moreover, we extend the ensemble calculation method to problems with open boundary conditions, with provable energy stability.